Perlindungan Hukum Terhadap Konsumen Peer To Peer Lending Atas Perbuatan Melawan Hukum Yang Dilakukan Oleh Debt Collector - Deza Pasma Juniar; Agus Suwandono; Helitha Novianty Muchtar (Universitas Widya Gama Malang, 2020)
The Financial Services Authority (OJK) in carrying out the regulatory function has regulated peer to peer lending in POJK No.77 / POJK.01/ 2016 (POJK LPMUBTI), but in the POJK LPMUBTI does not regulate the use of third parties or debt collector when collecting loans to consumers. This is only regulated in the Code of Conduct created by AFPI and there are still infringement by third parties or debt collectors peer to peer lending to consumers when collecting loans to consumers. This research is to analyse the regulation of the use of third parties or debt collectors in peer to peer lending when collecting loan to consumers and dispute resolution that can be done by consumers against debt collectors who commit unlawful acts in collecting loans. The method used in this article is normative juridical approach, which focuses on examining the implementation of written legal regulations and literatures. The results of this research shows that the Financial Services Authority has not yet regulated about the regulation of the use of debt collectors in peer to peer lending, it is only regulated in the Code of Conduct prepared by AFPI, so that it does not have a legal position thereby causing legal uncertainty. And it also shows that consumers can do dispute resolution in two steps, first complaint through the peer to peer lending providers and the second is through litigation process or non litigation process such as through the Alternative Dispute Resolution Institution (LAPS) provided by the OJK.